Novel Biomarkers of Heart Failure in Pediatrics - Teja Senekovič Kojc; Nataša Marčun Varda (MDPI AG, 2022)
Novel biomarkers of heart failure are the subject of numerous studies. Biomarkers of heart failure can be determined in the blood and in the urine. Seven groups of biomarkers of heart failure based on pathophysiological mechanisms are presented in this review, namely biomarkers of myocardial stretch, myocyte injury, myocardial remodeling, biomarkers of inflammation, renal dysfunction, neurohumoral activation, and oxidative stress. Studies of biomarkers in the pediatric population are scarce, therefore, further investigation is needed for reliable prognostic and therapeutic implications. The future of biomarker use is in multimarker panels that include a combination of biomarkers with different pathophysiological mechanisms in order to improve their diagnostic and prognostic predictive value.